Porphyrin Metalation at the MgO Nanocube/Toluene Interface - Schneider, Johannes; Kollhoff, Fabian; Bernardi, Johannes; Kaftan, Andre; Libuda, Jörg; Berger, Thomas; Laurin, Mathias; Diwaid, Oliver (ACS Applied Materials and Interfaces, 2015)
Molecular insights into porphyrin adsorption on nanostructured metal oxide surfaces and associated ion exchange reactions are key to the development of functional hybrids for energy conversion, sensing, and light emission devices. Here we investigated the adsorption of tetraphenylporphyrin (2HTPP) from toluene solution on two types of MgO powder. We compare MgO nanocubes with an average size d < 10 nm and MgO cubes with 10 nm <= d <= 1000 nm. Using molecular spectroscopy techniques such as UV/vis transmission and diffuse reflectance (DR), photoluminescence (PL), and diffuse reflectance infrared Fourier-transform (DRIFT) spectroscopy in combination with structural characterization techniques (powder X-ray diffraction and transmission electron microscopy, TEM), we identified a new room temperature metalation reaction that converts 2HTPP into magnesium tetraphenyl-porphyrin (MgTPP). Mg2+ uptake from the MgO nanocube surfaces and the concomitant protonation of the oxide surface level off at a concentration that corresponds to roughly one monolayer equivalent adsorbed on the MgO nanocubes. Larger MgO cubes, in contrast, show suppressed exchange, and only traces of MgTPP can be detected by photoluminescence.
Keywords: porphyrin metalation; MgO cubes; solid-liquid interface; molecular spectroscopies; dye adsorption; hybrid materials